Celebrating life and harmony : African theology as liberating wisdom in the Evangelical Lutheran Church in Botswana - Auvinen-Pöntinen, Mari-Anna. (Joensuu : University of Eastern Finland, 2011)
Abstrakti.
Väitöskirja
Keywords: African theology; luterilaisuus; teologia; vapautuksen teologia; kontekstuaalinen teologia; Afrikka